Implementasi Strategi Group to Group dan Crossword Puzzle Untuk Meningkatkan Hasil Belajar Fiqih. - Imam Bahroni; Nur Kholis (Educan : Jurnal Pendidikan Islam, 2017)
Arrisalah Islamic boarding school is one of the famous boarding school in East Java that teach both of Islamic learning and scientific learning. Fiqh lesson is one of important lessons that teach in that boarding school. Many strategies applied by teacher to teach student more easily.  Group to Group and Crossword Puzzle is impressive strategy that chosen by many teacher in Fiqh teaching. This research aim to (1) describes the implementation of Group to Group and Crossword Puzzle strategy to develop student’s learning activity in Fiqh lesson. (2) Describes the implementation of Group to Group and Crossword Puzzle strategy in Fiqh learning. (3) describe the student’s value improvement in Fiqh learning after implemented with Group to Group and Crossword Puzzle strategy. The research outcome shown that (1) the implementation of Group to Group and Crossword Puzzle strategy can increase student’s learning activity in Fiqh lesson. (2) The implementation of Group to Group and Crossword Puzzle strategy include in three steps, the opening, learning activity, and closing activity. (3) The improvement was found in student’s learning result of Fiqh lesson after implemented by Group to Group and Crossword Puzzle strategy.